INTEGRASI NILAI-NILAI KEADILAN SOSIAL DI PENDIDIKAN ANAK USIA DINI - Rista Erika (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The purpose of this article is to explain the importance of introducing social justice values in Early Childhood Education. Indonesia is a multicultural country, so social justice values are crucial to introduce from an early age. Social justice is a practice that does not silence diversity and differences. In learning practices in Early Childhood Education, the issue of social justice is still taboo. However, through a literature review approach and critical analysis, this article finds that social justice education can shape children into caring, tolerant, and just individuals from an early age. Children can maintain their cultural, racial, and ethnic differences. Strategies that can be used include the use of an inclusive curriculum, collaborative learning methods, and teacher training that is sensitive to social issues.